Aspectos citológicos da variabilidade genética em Glomerella cingulata (Stonem.) Spauld & Schrenck f. sp. phaseoli (Colletotrichum lindemuthianum (Sacc. & Magn) Scribner) - Magallanes, Maria Gabriela Roca (1997)
Resumo Indisponível.